2017
DOI: 10.1002/jmv.24819
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile after knockdown of USP18 in Hepg2.2.15 cells

Abstract: In our previous work, we found that the expression of ubiquitin-specific protease 18 (USP18), also known as UBP43, is associated with the efficiency of interferon alpha (IFN-α) treatment in patients with chronic hepatitis B (CHB). To elucidate the influence of USP18 on hepatitis B virus (HBV) replication and the mechanism of this activity, we silenced USP18 by introducing short hairpin RNA (shRNA) into Hepg2.2.15 cells. To identify the changed genes and pathways in Hepg2.2.15-shRNA-USP18 cells, we performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Our findings are in accordance with the studies on HBV infection and the immune process, in which the main enrichments were those corresponding to the innate and adaptive immunity responses. Additionally, we evaluated these DEGs by KEGG pathway analysis and identified 19 associated pathways, including the TGF-signaling pathway and complement and coagulation cascades, which are linked with cirrhosis in HBV infection and in hepatocellular carcinoma [31,32]. These results indicated that DGEs participate in HBVmediated progression of CHB to liver cirrhosis and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with the studies on HBV infection and the immune process, in which the main enrichments were those corresponding to the innate and adaptive immunity responses. Additionally, we evaluated these DEGs by KEGG pathway analysis and identified 19 associated pathways, including the TGF-signaling pathway and complement and coagulation cascades, which are linked with cirrhosis in HBV infection and in hepatocellular carcinoma [31,32]. These results indicated that DGEs participate in HBVmediated progression of CHB to liver cirrhosis and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, USP18 dampens the effects of type I and type III IFNs by exerting negative feedback control through its regulatory role ( 89 ). Moreover, USP18 also binds to and deubiquitinates TAK1, thereby promoting hepatic inflammatory responses ( 90 92 ).…”
Section: Roles Of Usps In Inflammatory Diseasesmentioning
confidence: 99%
“…Some studies have demonstrated that ubiquitin-specific protease 18 (USP18), known as UBP43, participates in gene regulations of the TH signaling pathway. Li et al, (2017 ) discovered that USP18 regulates the signaling of antivirus by the TH signaling pathway, prolactin signaling pathway, insulin resistance and complement, and have crosstalk among them. Also, the thyroid hormone-uncoupling protein (TRUP) gene and thyroid hormone receptor-associated protein 150 alpha gene are associated to the integration of HBV DNA into liver cell DNA, which are the key regulators of cell proliferation and viability ( Gozuacik et al, 2001 ; Paterlini-Bréchot et al, 2003 ).…”
Section: The Regulatory Mechanisms Underlying Th/tr Axis May Supply N...mentioning
confidence: 99%